2020
DOI: 10.1093/cid/ciaa1666
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Experience With Severe Acute Respiratory Syndrome Coronavirus 2–Related Illness in Children: Hospital Experience in Cape Town, South Africa

Abstract: Background Children seem relatively protected from serious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) related disease, but little is known about children living in settings with high tuberculosis and HIV burden. This study reflects clinical data on South African children with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods We collected clinical data of children aged younger than 13 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…A study conducted in South Africa among children younger than 13 years showed that among hospitalized children, majority were symptomatic, one-fifth had pre-existing medical condition and respiratory support was required in half of the children [17].…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in South Africa among children younger than 13 years showed that among hospitalized children, majority were symptomatic, one-fifth had pre-existing medical condition and respiratory support was required in half of the children [17].…”
Section: Introductionmentioning
confidence: 99%
“…One (2.3%) study did not specify the inclusion criteria [ 46 ]. Only two (4.7%) studies specifically evaluated children [ 63 , 71 ]; others included only adults or described a mixed population. Patient information was retrieved mainly from medical records at participating healthcare facilities, or from surveillance registries or insurance databases ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many authors appealed to elucidate the tangible influence of HIV and TB over COVID-19 severity, since resources were often scarce, with intensive care facilities completely full so the admission of patients had to be rationed [ 53 ]. This need of a thorough research was especially claimed for children, who represented a significant percentage of hospitalization in low- and middle-income countries, in particular sub-Saharan African countries [ 54 ]. Some COVID-19 surveillance studies and systems designed with the aim of determining the impact of HIV and TB on SARS-CoV-2 infection susceptibility, were ongoing or not finished yet [ 55 ].…”
Section: Resultsmentioning
confidence: 99%